Global Health Needs Modernized Containment Strategies to Prepare for the Next Pandemic - Seetah, Krish; Moots, Hannah; Pickel, David; Van Cant, Marit; Cianciosi, Alessandra; Mordecai, Erin; Cullen, Mark; Maldonado, Yvonne (Frontiers in Public Health, 2022)
Here we highlight the important role of anthropological and historical perspectives to inform approaches to non-pharmaceutical interventions to the Sars-Cov-2 pandemic and future preparedness. The National Academy of Medicine, a not-for-profit, non-governmental US-based medical watchdog organization, published a key document early in the Sars-Cov-2 pandemic which points to inadequate quarantine and containment infrastructure as a key obstacle to an effective pandemic response. In considering how to implement effective quarantine policies and infrastructure, we argue that it is essential to take a long-term approach to the interventions that have been effective in past pandemics while simultaneously addressing and eliminating the negative socio-historical legacies of quarantine practices.